Hubungan Tingkat Pengetahuan Ibu Tentang Gizi dengan Kejadian Stunting Balita 12-59 Bulan di Wilayah Kerja Puskesmas Tegallalang 1 - Ni Made Ayu Novita Anugerah; Luh Gede Pradnyawati; Anny Eka Pratiwi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The correlation between mother’s knowledge regarding nutrition with the prevalence of stunting among children aged 12-59 months within the area of Tegallalang I Primary Health Centre] Stunting is condition when a toddler exhibits a height or length that falls below the median standard growth set by WHO, with a deviation of more than minus two standard deviations. Stunting arises due to chronic malnutrition during the initial 1000 days of a child's life. The main aims of this research are to establish the correlation between the level of maternal comprehension regarding nutrition and the occurrence of stunting among toddlers aged 12-59 months within the jurisdiction of Tegallalang I Primary Health Centre, Gianyar Regency. The research methodology applied for this investigation is a quantitative analytical study with a case-control designs. The total sample size were 96 respondents, evenly divided between 48 cases and 48 controls. The sample technique employed is consecutive sampling for the control group and total sampling for the case group. The sampling methods was consecutive sampling to ensuring the inclusion of all qualifying subjects in attained the required sample size. Data were gathered through the assessment of height or length measurements and the completion of questionnaires. Data were analysed used chi-square analysis to examine the relationship between the mother’s knowledge of nutrition and stunting prevalence. The findings indicated a significant correlation betweens the mother knowledge about nutrition and the occurrence of stunting, with a significance level of < 0.001. As a result, mothers with inadequate nutritional knowledge may contribute to an increased risk of stunting in toddlers, as those with less knowledge experienced a 19.35-fold rise in stunting cases among toddlers aged 12 untill 59 months within the working area of Tegallalang I Primary Health Centre.